Analysis of Student Needs in Electrochemistry Learning Based on Culturally Responsive Transformative Teaching (CRTT) in Grade XII MIPA UM Laboratory High School - Widarti, Hayuni Retno; Sulistyorini, Dwi; Sumarsono, Raden Bambang; Setyowati, Istri; Rokhim, Deni Ainur; Juliandani, Fasha; Marestya, Alfina Dwi (Universitas Negeri Surabaya, 2025)
This study aims to analyze students’ learning needs in electrochemistry learning based on the Culturally Responsive Transformative Teaching (CRTT) framework. CRTT is a pedagogical approach that integrates students’ cultural backgrounds and lived experiences into learning to make it more inclusive and meaningful. The research employed a descriptive quantitative method complemented by qualitative data from open responses. A total of 32 Grade XII MIPA students from UM Laboratory High School participated in the study. Data were collected through a validated questionnaire consisting of 15 closed and 5 open-ended items. The results show that 64% of students have a moderate understanding of electrochemistry, with the most difficult subtopics being Galvanic and Electrolysis Cells. Students expressed strong interest (80%) in contextual learning through simple and eco-friendly edukits, as well as enthusiasm for integrating local culture such as keris plating and natural electrolytes from plants. These findings emphasize the importance of developing CRTT-based learning tools that connect chemical concepts with students’ cultural realities to foster deeper conceptual understanding, engagement, and transformative learning experiences.